Doppler Examination Informativity in Children with Chronic Viral Hepatitis - F. I. Inoyatova; G. A. Yusupalieva; G. Z. Inogamova (Детские инфекции (Москва), 2015)
In this article presents the data of ultrasound examination of 150 children with chronic hepatitis В (ChHB). Ultrasound research which combined with clinical and laboratory data do not always reflect the true picture of the pathological process in the liver, while differences may vary between 14—37%. It is shown that the inclusion of additional Doppler echography in allow not only improve the efficiency of diagnosis of ChHB activity (by 35.3%), but also broaden our understanding about the state of the parenchyma of the liver and spleen, collateral circulation disorders and severity of portal hypertension. Regardless of the age, set to the same orientation of structural and functional disorders of hepatic vessels, the basic and indirect diagnostic criteria of portal hypertension has been developed.